Barriers to Abortion among Women and Girls in Selected Districts of Nepal - Phuyal, Parash Prasad; Bhattarai, Tejaswee; Pant, Prakash Dev; Devkota, Bishnu; Devkota, Jivan; Dhakal, Madhav Prasad; Karki, Sujan; Ghimire, Jagadishwor; Moore, Brittany (Journal of Nepal Health Research Council, 2024)
Background: Even after two decades of legalization of abortion in Nepal, most women and girls still do not have knowledge on abortion legality and face abortion barriers. This study will explore perceived barriers to safe abortion and the factors associated with it.Methods: A Mixed method study design was conducted in 30 wards of 20 Municipals of seven districts of Lumbini and Sudurpaschim provinces. Quantitative data was analyzed for 673 women of reproductive age of 15-49 years. For qualitative data, key informant interviews were conducted. The analysis was done on five different barriers and a composite variable was created from them. Results: Most women and girls perceived social (34.6%), followed by family (30.6%), physical (30.6%), personal (29.5%), and health facility (14.9%) barriers to access safe abortion services. The key finding was that women and girls with knowledge on abortion legality were more likely to perceive barriers to abortion (AOR:2.31, CI:1.574-3.394). Women and girls with higher educational and economic status as well as Dalit women were less likely to perceive barriers to abortion services whereas never married women and girls perceived more barriers in accessing abortion services.Conclusions: Women and girls perceived several barriers to access safe abortion services. Women who have better knowledge on abortion legality recognize more barriers regarding abortion. This highlights the importance of raising awareness of women and girls on abortion rights to empower them in recognizing and advocating for the removal of the obstacles that stop them from getting abortion services.Keywords: Barriers to abortion; caste/ethnicity; legal knowledge; women and girls.